THE RELATIONSHIP BETWEEN CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE - Kamola , Yusufova; Sari, Maya; Qudratov, Inomjon (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2026)
In corporate management, corporate governance is a framework that integrates accountability and control Long-term competitiveness and better financial performance are directly impacted by this system. The purpose of this literature study is to determine how important corporate governance mechanisms such as board composition, ownership concentration, CEO tenure, audit committees, internal control, and information disclosure transparency affect financial performance. The consequences of governance change for businesses and decision-makers in emerging nations like Uzbekistan are also examined in this research. The sources used in this study's structured thematic evaluation were chosen based on their applicability to agency theory, governance systems, and developing market financial performance. The evolution of the financial sector, state ownership structure, and governance circumstances are contextualised by integrating World Bank reports on Uzbekistan with scholarly literature.This analysis demonstrates how effective company governance enhances financial performance by lowering agency costs, increasing capital availability, enhancing the calibre of strategic choices, and boosting investor trust. But this impact is also influenced by the institutional setting. Concentrated ownership can improve monitoring but also increase the risk of conflicts of interest, therefore having an independent board of directors is not always beneficial. Moreover, disclosure regulations work best when they are backed by reliable enforcement. Crucially, when governance measures operate as an integrated system rather than a compliance checklist, the best financial performance is attained. These conclusions apply to businesses and officials seeking governance reform in developing nations, such as Uzbekistan, where investor protection is inadequate, state ownership is still predominant, and disclosure procedures are applied unevenly.